(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2025)
Objective: The main aim of this project is to formulate and in vitro evaluation of effervescent drug delivery using Propanolol HCl as a model drug. Methodology: The effervescent floating drug delivery was prepared using hydrophilic polymer in two different grades, HPMC K4M and HPMC K200M. Sodium carbonate is used as a gas-generating agent in floating tablets. The tablets were prepared by the wet granulation method. The ratio of HPMC to ethyl cellulose was kept constant at 2:1. The formulated tablets were evaluated for physicochemical properties, in vitro buoyancy, floating properties, swelling studies, in vitro dissolution studies, and drug release kinetics. Results: The result of in vitro dissolution showed that the sustained release can be achieved using HPMC and increasing the concentration of hydrophilic polymers like HPMC K4M and HPMC K200M increases the capacity of holding the drug within the polymer for a longer time. However, changing the viscosity of the HPMC had no significant difference in the drug release profile. The floating lag time for all the formulations was found to be less than 2 minutes with a floating time of more than 24 hours which showed the adequate buoyancy of the tablets. Conclusion: The present studies showed that using hydrophilic polymers like HPMC K4M and HPMC K200M along with ethyl cellulose and sodium carbonate as gas generating agents can be used for developing sustained released effervescent floating tablets.